2016
DOI: 10.1136/neurintsurg-2016-012265
|View full text |Cite
|
Sign up to set email alerts
|

Statins are not associated with short-term improved aneurysm healing in a rabbit model of unruptured aneurysms

Abstract: Systemic statin administration after platinum coil embolization of unruptured aneurysms in a rabbit model does not improve aneurysm occlusion rates at 4 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…[29] In a systematic review and meta-analysis of 102 studies describing 144 risk factors, there was strong evidence for the morphological factors, including size ratio, to increase rupture risk. [30] The results of our univariate model indicated that an aSR ≥3 is a factor associated with RIA. Despite the lack of significant results in the multivariate model, the RF model indicates that after the IA location, the aSR is one of the most informative variables in predicting ruptures.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…[29] In a systematic review and meta-analysis of 102 studies describing 144 risk factors, there was strong evidence for the morphological factors, including size ratio, to increase rupture risk. [30] The results of our univariate model indicated that an aSR ≥3 is a factor associated with RIA. Despite the lack of significant results in the multivariate model, the RF model indicates that after the IA location, the aSR is one of the most informative variables in predicting ruptures.…”
Section: Discussionmentioning
confidence: 73%
“…[29] The supposed mechanisms involved their anti-inflammatory effects and their ability to stimulate the production of the extracellular matrix and the chemotactic migration of mesenchymal progenitor cells to stabilize the IA's parietal layers. [30] Interestingly, the largest case-control study to date, which involved 4701 patients with 6411 IAs, showed that use of a lipid-lowering agent was significantly inversely associated with RIA. [31] Subjects enrolled in the International Study of Unruptured Intracranial Aneurysms were compared regarding the frequency of aspirin use.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have reported con icting results. For example, statin medication did not improve the healing rate of aneurysms in a rabbit model of unruptured aneurysms [21]. Additionally, a single-center case-control study including 1200 patients showed no signi cant bene cial effect of statin medication on IA inhibition [22].…”
Section: Discussionmentioning
confidence: 95%
“…[ 150 ] 2016 X Surgical Rabbits Saccular X Ding Y.H. [ 151 ] 2016 X Surgical Rabbits Saccular X Brinjikji W. [ 152 ] 2017 X Surgical Rabbits Saccular X Fahed R. [ 153 ] 2017 X Surgical Dogs Saccular X Miyamoto T. [ 154 ] 2017 X Endogenous Rats Saccular X …”
Section: Methodsmentioning
confidence: 99%